Endocarditis-Induced Mycotic Brain Aneurysm following Right MCA Stroke. (12th April 2012) - Allen, Brandon; Desai, Bobby; Falgiani, Michael
Abstract : The diagnosis of cerebrovascular accident is extremely common in emergency medicine; however, CVA resulting from hemorrhage following mycotic brain aneurysm following embolic stroke is extremely uncommon. This case reports such an event.